Mathematics for economics and finance : methods and modelling - Anthony, Martin (New York, 1996)
This book is an introduction to calculus and linear algebra for students of disciplines such as economics, finance, business, management, and accounting. It is intended for readers who may have already encountered some differential calculus, and it will also be appropriate for those with less experience, possibly used in conjunction with one of the many more elementary texts on basic mathematics. Parts of this book arise from a lecture course given by the authors to students of economics, management, accounting and finance, and management sciences at the London School of Economics.
Keywords: Mathematical economics